Improving the Students’ Reading Comprehension Achievement by Using Mapping Technique at Ilmu Al-Qur’an and Tafsir (IAT1) IAIN Jember - Rojabi, Ahmad Ridho (Universitas PGRI Adi Buana Surabaya, 2018)
This research was aimed at improving the ability of the students of IAT-1 in reading comprehension achievement by implementing mapping technique. To achieve the purpose, the classroom action research design was employed by following four stages: planning, implementing, observing, and reflecting. This research was implemented in two cycles, in which both the first cycle and the second cycle were carried out in two meetings. Mapping as a teaching technique can help students visualize the basic shape of material, the main ideas and details about a topic, and how the topic, main ideas, and details are related each other in some sort of illustration (boxes, circles, connecting lines, diagram). The characteristics of mapping are; hierarchy, diagram, compare and contrast, timeline, processes or cycles. The result of the research revealed that mapping technique improved the students‟ reading comprehension achievement of IAT-1 IAIN Jember.